COMPARATIVE EVALUATION OF GARDEN PEA VARIETIES OF TWO MORPHOTYPES ACCORDING TO A SET OF TRAITS IN KRASNODAR REGION - O. V. Alikina; A. G. Besedin; O. V. Putin; M. A. Vishnyakova (Труды по прикладной ботанике, генетике и селекции)
In 2014-15, evaluated in Krasnodar Region were the yield of green pea, net productivity of photosynthesis, productivity of a foliage surface unit as well as the economic coefficient in 16 garden pea varieties of the common leafy and leafless morphotypes. The study helped to identify leafless varieties comparable with those of the conventional morphotype accordin to the set of traits studied.